Strategic management of space sector stakeholders - Silva, Isomar Lima da; Muro, Bruno da Silva; Silva, José Wagner da (Seven Editora, 2023)
This article aims to analyze the power of stakeholders in the strategic management of companies in the space sector, for which 6 companies were analyzed. Initially, the identification of its stakeholders was carried out based on the (Mitchell, Wood, and Agle 1997) methodology, which considers the ownership or the attributed ownership of one, two, or the three attributes: power, legitimacy, and urgency, to define the class to which the stakeholder belongs. The combination of the attributes allowed us to know seven types of stakeholders. The results were obtained through case-by-case analysis and comparison of cases between them. The analyzed data reveal the managers’ perception of the importance and influence of stakeholders for the organization, in addition to showing us that these two factors are closely linked to an organization’s stakeholders, and their ability to handle restrictions and requirements to be placed in practice in strategic management. DOI:https://doi.org/10.56238/devopinterscie-262